Kinetika Reaksi Pembentukan Furfural Dari Sekam Padi (Oryza Sativa) Dengan Two-Stage Method - Siahaan, Joshua Theo Anugerah; Achmad Aris Syahrul Ramadhan; Kindriari Nurma Wahyusi (Jurnal Serambi Engineering, 2025)
Furfural is a valuable furan-based organic compound widely used in the chemical and pharmaceutical industries, and as an intermediate in the production of furfuryl alcohol and furanone. However, Indonesia still relies on imports due to the absence of local furfural producers. Rice husk, an abundant agricultural waste rich in pentosan, offers promising potential as an alternative raw material. This study aims to determine the kinetic equation for furfural formation from rice husk (Oryza sativa) using a two-stage method with sulfuric acid as a catalyst. The process involves hydrolysis of pentosan into pentose, followed by dehydration into furfural. Temperature (80–100 °C) and reaction time (20–60 minutes) variations were applied to observe their effect on furfural concentration, analyzed using the iodometric titration (Excess Iodine Method). Results show that the reaction follows first-order kinetics, with linear graphs and R² values approaching 1. Furfural concentration increased with both temperature and time. The activation energy obtained was 21.62 kJ/mol and the pre-exponential factor (k₀) was 14.26. This study confirms that the two-stage method is more effective in enhancing furfural production from rice husk biomass.